Efektivitas Pijat Perineum dan Peanut Ball dengan Kemajuan Persalinan di Rumah Sakit Dr. R Soeharsono Banjarmasin Tahun 2025 - Arum Winarsih; Hapisah Hapisah; Zakiah Zakiah (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
Background: Normal labor is influenced by Power, His, maternal strength, external pelvic passage, pelvic shape, pelvic width, and perineal elasticity, which affect labor.Objective: To determine the effect of perineal massage and peanut ball on labor progress.Method: This study used a quasi-experimental design with two groups and a posttest only. The sample consisted of 30 mothers in labor, divided into two groups: 15 respondents received perineal massage and 15 respondents received perineal massage and used a peanut ball. Data were analyzed using an Independent T-Test. Results: The study showed that the average duration of the first stage of active labor in the perineal massage group was 6.87 hours, while in the combination group of perineal massage and peanut ball it was 5.20 hours. Statistical testing showed a value of p = 0.012 (p < 0.05), indicating a significant difference between the two groups. Conclusion: Perineal massage and peanut balls are effective in accelerating labor as non-pharmacological midwifery interventions in labor management.